Maternal demand for cesarean section: perception and willingness to request by Nigerian antenatal clients - Okonkwo NS; Ojengbede OA; Morhason-Bello IO; Adedokun BO (Dove Medical Press, 2012)
Ngozi S Okonkwo1, Oladosu A Ojengbede2, Imran O Morhason-Bello1, Babatunde O Adedokun31Department of Obstetrics and Gynecology, University College Hospital; 2Center for Population and Reproductive Health, College of Medicine, University of Ibadan, Ibadan; 3Department of Epidemiology, Medical Statistics, and Environmental Health, College of Medicine, Ibadan, Oyo State, NigeriaBackground: Contrary to the widely reported aversion to cesarean section in the West African subregion, maternal demand for cesarean section (MDCS) seems to be on the increase, and there is little evidence to explain this trend. The purpose of this study was to determine the perception and attitudes of Nigerian antenatal clients towards MDCS, their willingness to request MDCS, and the relationship between willingness to request MDCS and sociodemographic characteristics.Methods: A cross-sectional survey was undertaken among 843 antenatal clients at Agbongbon/Orayan primary health care centers (PHCs), Adeoyo Maternity Hospital (SHC), and UCH Ibadan (THC), representing the three different levels of health care in Nigeria, ie, primary, secondary, and tertiary.Results: The proportion of women aware of MDCS was 39.6%. Predictors of awareness were education and type of health facility. Women from THC and those with tertiary education and above were more likely to be aware of MDCS than others (P = 0.001). Doctors were major sources of information on MDCS (30.8%) as well as friends (24.3%). Common reasons reported for MDCS were fear of labor pains (68.9%), and fear of poor labor outcome (60.1%), and fear of fecal (20.2%) and urinary incontinence (16.8%). More women from the THC than other facilities believed that requests for MDCS should be granted (P < 0.001). However, willingness to request MDCS was low (6.6%). More than 50% of those willing to request MDCS would likely be criticized, mainly by their husbands. On multiple logistic regression, respondents at the THC were significantly more likely than those at the SHC or the PHCs to request cesarean section and to favor a woman’s right of autonomy to choose her mode of delivery.Conclusion: The decision for MDCS is a difficult one, because willingness is low and criticism by partners of those who choose MDCS is high. Provision of epidural anesthesia and improved safety of vaginal delivery is recommended. This may prevent Nigerian women from making a difficult choice for MDCS based on fear of pain and poor labor outcome. The role of the male partner should be taken into consideration in order to make sustainable policies or guidelines for MDCS in developing countries.Keywords: maternal demand cesarean section, perception, antenatal, clients, Nigeria